A case of transient existence of SARS-CoV-2 RNA in the respiratory tract with the absence of anti-SARS-CoV-2 antibody response. (July 2020) - Lin, Yi-Chun; Cheng, Chien-Yu; Chen, Cheng-Pin; Cheng, Shu-Hsing; Chang, Sui-Yuan; Hsueh, Po-Ren
Highlights: We report a case of transient existence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) RNA in the respiratory tract with the absence of an anti-SARS-CoV-2 antibody response. SARS-CoV-2 RNA was absent in the six respiratory specimens that were subsequently tested. Anti-SARS-CoV-2 IgM and IgG were absent in the acute and convalescent sera. Abstract: We report the case of a patient who had travelled to Japan and who presented mild respiratory symptoms during the COVID-19 outbreak period. There was transient existence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) RNA in his oropharynx. The RNA was absent in the six respiratory specimens that were subsequently tested. An anti-SARS-CoV-2 antibody response was absent in the acute and convalescent sera. The reported case indicates that transient colonization of SARS-CoV-2 in the upper respiratory tract is possible without inciting any antibody response against the virus.